let A, B be category; :: thesis: for C being non empty subcategory of A
for F being covariant Functor of A,B
for a, b being Object of A
for c, d being Object of C st c = a & d = b & <^c,d^> <> {} holds
for f being Morphism of a,b
for g being Morphism of c,d st g = f holds
(F | C) . g = F . f

let C be non empty subcategory of A; :: thesis: for F being covariant Functor of A,B
for a, b being Object of A
for c, d being Object of C st c = a & d = b & <^c,d^> <> {} holds
for f being Morphism of a,b
for g being Morphism of c,d st g = f holds
(F | C) . g = F . f

let F be covariant Functor of A,B; :: thesis: for a, b being Object of A
for c, d being Object of C st c = a & d = b & <^c,d^> <> {} holds
for f being Morphism of a,b
for g being Morphism of c,d st g = f holds
(F | C) . g = F . f

let a, b be Object of A; :: thesis: for c, d being Object of C st c = a & d = b & <^c,d^> <> {} holds
for f being Morphism of a,b
for g being Morphism of c,d st g = f holds
(F | C) . g = F . f

let c, d be Object of C; :: thesis: ( c = a & d = b & <^c,d^> <> {} implies for f being Morphism of a,b
for g being Morphism of c,d st g = f holds
(F | C) . g = F . f )

assume that
A1: ( c = a & d = b ) and
A2: <^c,d^> <> {} ; :: thesis: for f being Morphism of a,b
for g being Morphism of c,d st g = f holds
(F | C) . g = F . f

let f be Morphism of a,b; :: thesis: for g being Morphism of c,d st g = f holds
(F | C) . g = F . f

let g be Morphism of c,d; :: thesis: ( g = f implies (F | C) . g = F . f )
assume g = f ; :: thesis: (F | C) . g = F . f
then A3: (incl C) . g = f by ;
( (incl C) . c = a & (incl C) . d = b ) by ;
hence (F | C) . g = F . f by ; :: thesis: verum